Burden of HPV-positive oropharynx cancers among ever and never smokers in the U.S. population. (September 2016) - Chaturvedi, Anil K.; D'Souza, Gypsyamber; Gillison, Maura L.; Katki, Hormuzd A.
Highlights: Smoking is a significant risk factor for both HPV-positive and HPV-negative oropharynx cancers. The burden of HPV-positive oropharynx cancers is higher in ever-smokers vs. never-smokers. The high burden of HPV-positive oropharynx cancers among smokers has clinical implications. Summary: Background: HPV-positive oropharynx cancer is frequently characterized as a disease of never-smokers due to higher HPV prevalence in oropharynx tumors among never-smokers than ever-smokers. We sought to estimate the burden (incidence rates and case counts) of HPV-positive oropharynx cancers among never, former, and current smokers in the US population by combining data from several sources. Methods: We decomposed the SEER population-level incidence of oropharynx cancers into rates among never-, former-, and current-smokers using a formula based upon rate ratios (RR) for the smoking-oropharynx cancer association (NIH-AARP cohort study) and smoking prevalence in the U.S. population (NHANES 2007/2008). These rates were multiplied by smoking strata-specific HPV prevalence in oropharynx cancer patients (RTOG0129) to estimate incidence of HPV-positive and HPV-negative oropharynx cancers, which were applied to the US population of smokers to calculate annual case counts. Analyses were conducted overall and gender-stratified. Results: The incidence of HPV-positive oropharynx cancers was significantly higher among ever versus never-smokers in the US population aged 20+ years during 2007/2008 (RR = 1.81; 95%CI = 1.32–2.47), including significantly higher incidence in current smokers (RR = 2.26; 95%CI = 1.60–3.21) and former smokers (RR = 1.38; 95%CI = 1.02–1.85). Of the estimated 6677 (5418 in men and 1259 in women) annually incident HPV-positive oropharynx cancers in the U.S during 2007/2008, 63.3% arose among ever smokers and 36.7% among never-smokers ( p < 0.001). In both men and women, incidence rates and annual cases of HPV-positive oropharynx cancers were higher in ever smokers versus never smokers. Conclusions: The population-level burden of HPV-positive oropharynx cancers is significantly higher among ever-smokers than never-smokers in the U.S.